Appraising administrative capability for development : a methodological monograph - International Group for Studies in National Planning; United Nations (New York : United Nations, 1969)
The ability of a governmental organisation to formulate and execute development plans and projects depend in large part on its administrative capability
"United Nations publication. Sales no.: E.69.II.H.2."
At head of title: Dept. of Economic and Social Affairs, Public Administration Division.
Includes bibliographical references.
obn 24/01/2019
Loans
Keywords: Public administration; Management